Effects of Dietary Protein Sources on Vitellogenin of Female Largemouth Bass (Micropterus salmoides) - Yue Tan; Yang Xu; Li Jia; Youqin Kong; Zhili Ding; Changle Qi; Qiyou Xu (Fishes, 2026)
To investigate the effects of three alternative protein sources—Hermetia illucens larvae meal (HIM), Chlorella meal (CM) and stickwater meal (SWM)—on the vitellogenin in female largemouth bass (Micropterus salmoides), these protein sources were used to replace 0% (control group, FM; containing 40% fishmeal), 25% and 50% of the fishmeal in the diet. A total of seven isonitrogenous and isolipidic diets were formulated (FM, 25% HIM, 50% HIM, 25% CM, 50% CM, 25% SWM and 50% SWM). The healthy female fish with an initial body weight of 353.57 ± 28.12 g were fed the experimental diets for eight weeks. The results showed that the viscerosomatic index, gonadosomatic index and oocyte diameter of broodstock in the 50% HIM group were significantly higher than those in the FM group. The 50% HIM group showed the highest rate of stage IV oocytes and the lowest share of stage II oocytes. Hepatic vitellogenin (Vg) mRNA expression was significantly upregulated in the 50% HIM group, whereas ovarian mRNA expression of Vg and vitellogenin receptor (VgR) was significantly upregulated in the 25% SWM and 50% SWM groups. In conclusion, replacing 50% of dietary fishmeal with Hermetia illucens larvae meal can promote ovarian development in largemouth bass broodstock by increasing the gonadosomatic index and the expression of genes involved in vitellogenin synthesis.